1995
DOI: 10.1002/jmri.1880050521
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of ovarian cancer

Abstract: Cross sectional imaging continues to play an increasingly important role in ovarian cancer diagnosis, staging, and treatment follow-up. Screening for ovarian cancer remains a controversial subject. The combined use of clinical examination, CA-125, and endovaginal ultrasound (US) are being advocated for high risk patients but consensus recommendation for screening awaits further studies. In characterization of an ovarian neoplasm US is indisputedly the primary imaging approach. Only when US is inconclusive are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 61 publications
0
12
0
1
Order By: Relevance
“…Unfortunately, gynecologic oncologists see less than half of ovarian cancer patients [46]. Is has been reported that up to 40% of cases are thought to actually be of a lower stage than they determined to be at their initial laparotomy [1,47,48,49]. Whatever the modality used, the correct staging of ovarian cancer with imaging studies is important in the determination of the appropriate referral to gynecologic oncologists, and thus to obtain a longer survival [18].…”
Section: Management Strategymentioning
confidence: 97%
“…Unfortunately, gynecologic oncologists see less than half of ovarian cancer patients [46]. Is has been reported that up to 40% of cases are thought to actually be of a lower stage than they determined to be at their initial laparotomy [1,47,48,49]. Whatever the modality used, the correct staging of ovarian cancer with imaging studies is important in the determination of the appropriate referral to gynecologic oncologists, and thus to obtain a longer survival [18].…”
Section: Management Strategymentioning
confidence: 97%
“…However, secondary findings suggestive of malignancy such as pelvic organ and pelvic side wall invasion; peritoneal, omental, or mesenteric involvement; ascites; and lymphadenopathy increase the confidence in a diagnosis of malignancy (10). When these secondary criteria are used in addition to the primary criteria, the reported accuracy of CT in characterization of ovarian tumors as benign versus malignant is 92%-94% (39,41).…”
Section: Local Extensionmentioning
confidence: 97%
“…The proportion of malignant tumors increases with age: Before 20 years of age, malignant tumors represent 4% of all ovarian neoplasms; however, after 50 years of age, this proportion increases to 40% (8). The germ cell tumors represent two-thirds of ovarian malignancies in females less than 20 years of age (10). This article focuses on the evaluation of epithelial ovarian tumors.…”
Section: Classification Of Primary Ovarian Tumorsmentioning
confidence: 99%
“…Although the entire abdomen and pelvis are explored, certain sites are difficult to evaluate at surgery. These sites are the diaphragm, splenic hilum, stomach, lesser sac, liver, and mesenteric root and the paraaortic nodes above the renal vessels (3,7). Consequently, detection of lesions at these sites is clinically helpful.…”
Section: Role Of Imagingmentioning
confidence: 98%
“…The majority of women have advanced disease at presentation (7). Tumor is limited to the ovaries in stage I disease and extends into the pelvic tissues in stage II disease; there are extrapelvic implants in stage III disease and distant or parenchymal liver metastases in stage IV disease (Table 1) (8).…”
Section: Clinical Backgroundmentioning
confidence: 99%